2020
DOI: 10.1080/1547691x.2020.1829211
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium induces CCL2 production in glioblastoma cells via activation of MAPK, PI3K, and PKC pathways

Abstract: Cadmium (Cd) is accumulated in human astrocytes and induces the production of interleukin (IL)-6 and IL-8. Astrocytes are one of the major sources of chemokine CC motif ligand 2 (CCL2; known as monocyte chemoattractant protein-1 [MCP-1]), in the brain. Elevated CCL2 levels are associated with cognitive impairment as well as the migration and invasion of glioblastoma cells. The present study hypothesized that non-toxic concentrations of Cd (as cadmium chloride [CdCl 2 ]) could up-regulate CCL2 production in U-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A recent study reported that acute exposure of Cd has a pro-inflammatory effect on human adipocytes ( Gasser et al, 2022 ). An additional study reported acute Cd exposure caused an upregulation of MCP-1 mRNA expression levels in glioblastoma cell lines ( Kasemsuk et al, 2020 ). Moreover, chronic low dose exposure to Cd was found to induce inflammatory infiltration in hepatocytes with an upregulation of MCP-1 mRNA expression level in the pubertal mice model ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that acute exposure of Cd has a pro-inflammatory effect on human adipocytes ( Gasser et al, 2022 ). An additional study reported acute Cd exposure caused an upregulation of MCP-1 mRNA expression levels in glioblastoma cell lines ( Kasemsuk et al, 2020 ). Moreover, chronic low dose exposure to Cd was found to induce inflammatory infiltration in hepatocytes with an upregulation of MCP-1 mRNA expression level in the pubertal mice model ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%